KEMAMPUAN PUBLIC SPEAKING GURU DALAM MEMOTIVASI PRESTASI BELAJAR SISWA DI MASA PANDEMI COVID-19 - Reza Andriana Dewanti; Agus Naryoso; Joyo Nur Suryanto Gono (Interaksi Online, 2022)
Distance Learning (PJJ) arises because of the Pandemi Covid-19, and in its implementation, PJJ is considered to reduce the motivation of student learning in Indonesia, seen from the impairment of academic grades of high school students in several schools in Indonesia. The role of the public speaking capability that teachers have is crucial, because if the teacher has a good public speaking capabilities in teaching, it will be able to increase the motivation of their students to study. But in reality, there are still many cases and assumptions about the public speaking ability of teachers who are still far from expectations, especially during this Distance Learning (PJJ) era, which can be one of the problems of education in Indonesia. This study aims to explain how the experience of teachers using public speaking skills in motivating student achievement during the Covid-19 pandemic, using qualitative methods and a phenomenological approach. Theory and concept used to support this research are the Rhetorical Theory and Persuasive Communication. The data collection method used was interviews and observation, with 6 informants consisting of 1 public and 1 private high school teachers, 2 state high school students, and 2 private high school students who were conducting teaching and learning activities, both online and face to face during the Covid-19 pandemic. The results of this study found that during Distance Learning (PJJ), the teacher's teaching load was indeed increased, but the experience of teachers using their public speaking skills in teaching during this pandemic as a whole has fulfilled all three rhetorical evidences from Aristotle, namely ethos, pathos, and logos. Each teacher in a school with different categories and conditions of students, in this case the superior and non-superior schools have different persuasive ways or approaches in teaching. The inhibiting factors for student learning motivation during the Covid-19 pandemic are the feeling of laziness, boredom, fatigue that appears when school is online, the lack of interaction between teachers and students, the influence of social media and games, and signal disturbances during school.